What do you think, Feezal? - Honey, Elizabeth ([St. Leonards, N.S.W.] : Allen & Unwin, 1997)
Bean has moved to Sydney, where her parents lead busy, fashionable lives, and she is lonely. But adventure strikes when she surprises the security guard raiding her father's computer. She is Read more...